STRATEGY OF CASH WAKAF TO IMPROVE THE ECONOMIC STABILITY OF VILLAGE COMMUNITIES - Gilang Samudra; Dzikri Abazis Subekti; Yupi Pirdayanti; Taufik Hidayat; Sri Mauludiyah (Gunung Djati Conference Series, 2025)
This study aims to analyze the strategy of cash waqf as an instrument in increasing the economic stability of rural communities. Cash waqf is one form of waqf that is now developing as a sustainable financing solution for the community, especially in rural areas that often face limited access to business capital. The study used a qualitative method with a descriptive analysis approach. Data analysis techniques were carried out through three stages, namely data reduction, data presentation and conclusions. The results of the study revealed that cash waqf that is managed professionally and transparently has an important role in providing sustainable financing sources for productive rural community businesses. With good management, cash waqf funds can be used to finance various economic activities such as agriculture, micro-enterprises, and small trade which are the backbone of the village economy. An effective cash waqf management strategy involves active community participation in decision-making and program implementation, as well as establishing synergy with Islamic financial institutions to maximize benefits and maintain sharia principles in fund management.